2013
DOI: 10.1111/rec.12021
|View full text |Cite
|
Sign up to set email alerts
|

Does Seeding After Wildfires in Rangelands Reduce Erosion or Invasive Species?

Abstract: Mitigation of ecological damage caused by rangeland wildfires has historically been an issue restricted to the western United States. It has focused on conservation of ecosystem function through reducing soil erosion and spread of invasive plants. Effectiveness of mitigation treatments has been debated recently. We reviewed recent literature to conduct a meta-analysis of seeding after wildfires to determine if seedings may (1) protect ecosystems against soil erosion and (2) reduce invasion or abundance of unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 44 publications
4
32
0
Order By: Relevance
“…4B) relative to burned areas where no rehabilitation was attempted. These results are consistent with a recent meta-analysis conducted by Pyke et al (2013) where they found post-fire rehabilitation efforts (either aerial or drill seeding) reduced cover of invasive species in only 26% of cases studied. It is possible some of the rehabilitation approaches applied following the MFF were more successful than others; however the low number of BR plots and variety of rehabilitation approaches applied does not allow us to compare among rehabilitation approaches here.…”
Section: Evaluation Of Rehabilitation Successsupporting
confidence: 82%
“…4B) relative to burned areas where no rehabilitation was attempted. These results are consistent with a recent meta-analysis conducted by Pyke et al (2013) where they found post-fire rehabilitation efforts (either aerial or drill seeding) reduced cover of invasive species in only 26% of cases studied. It is possible some of the rehabilitation approaches applied following the MFF were more successful than others; however the low number of BR plots and variety of rehabilitation approaches applied does not allow us to compare among rehabilitation approaches here.…”
Section: Evaluation Of Rehabilitation Successsupporting
confidence: 82%
“…Part 1, Literature Review (Pyke et al 2013) Nineteen published studies specifically measured the abundance of invasive plant species following postfire seeding, and eight measured soil erosion. All these studies were at least medium quality, i.e., had adequate unseeded controls.…”
Section: Key Findingsmentioning
confidence: 99%
“…Part 1, Literature Review (Pyke et al 2013) This review was conducted using methods described in Pullin and Stewart (2006). We searched for literature dealing with postfire seeding of rangelands worldwide.…”
Section: Study Description and Locationmentioning
confidence: 99%
“…As expected, there is heated debate as to the overall environmental benefit and ecological ethics associated with using nonnatives for revegetation projects (Davison and Smith 1996;Pyke et al 2013). Researchers acknowledge that many ecological habitats cannot return to the traditional native reference states that often form the basis of restoration project designs (e.g., Egan and Howell 2001).…”
mentioning
confidence: 99%
“…The rapid establishment rate of nonnatives is useful for erosion control in high-stress environments where soil destabilization is typical or revegetating landscapes exposed to intense wildfire (Pyke et al 2013). The presence and persistence of nonnatives might also be facilitated more by changing environmental conditions than natives through, for example, altered introduction mechanisms (Hellmann et al 2008).…”
mentioning
confidence: 99%